KEEFEKTIFAN PENERAPAN CHEMISTRY GOLDEN BELL TERHADAP MOTIVASI DAN PRESTASI BELAJAR KIMIA PESERTA DIDIK - MUJIYAH MUJIYAH (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2022)
This study aims to determine whether there is a significant difference in the motivation and learning achievement of chemistry students of class X SMKN 1 Krangkeng who take lessons using the Chemistry Golden Bell (CGB) technique and learning without the CGB technique if the prior knowledge of chemistry is controlled statistically. The research design used one factor, two samples and one covariable. The population of the study was the 69th grade students of TKJ SMKN 1 Krangkeng divided into 3 classes. The research sample was 46 students taken by purposive sampling divided into 2 classes, the experimental class was 22 samples and the control class was 24 samples. The data obtained in this study were data on prior knowledge of chemistry, motivation to learn chemistry, achievement in learning chemistry and data on the effectiveness of the implementation of CGB techniques. The data on students' chemistry learning motivation were analyzed using t-test, students' chemistry learning achievement data were analyzed using covariance analysis, and the effectiveness of the implementation of the CGB technique was analyzed using score conversion to a scale value of 5. The results showed no significant differences in motivation and learning achievement. students who take part in learning with the CGB technique and learning not with the CGB technique. The application of the CGB technique in the implementation of learning is quite effective in achieving learning objectives, judging from the results of filling in the observation sheet and respondent sheet for the effectiveness of the implementation of learning. ABSTRAKPenelitian bertujuan  mengetahui ada tidaknya perbedaan yang signifikan pada motivasi dan prestasi belajar kimia peserta didik kelas X SMKN 1 Krangkeng yang mengikuti pembelajaran dengan teknik Chemistry Golden Bell (CGB) dan pembelajaran tidak dengan teknik CGB jika pengetahuan awal kimia dikendalikan secara statistik. Desain penelitian menggunakan satu faktor dua sampel dan satu kovariabel. Populasi dari penelitian adalah peserta didik kelas X TKJ SMKN 1 Krangkeng berjumlah 69 terbagi dalam 3 kelas. Sampel penelitian sebanyak 46 peserta didik diambil secara purposive sampling  terbagi dalam 2 kelas, kelas eksperimen 22 sampel dan kelas kontrol 24 sampel. Data yang diperoleh dalam penelitian ini adalah data pengetahuan awal kimia, motivasi belajar kimia,prestasi belajar kimia dan data keefektifan pelaksanaan teknik CGB. Data motivasi belajar kimia peserta didik dianalisis menggunakan uji-t, data prestasi belajar kimia peserta didik dianalisis dengan menggunakan analisis kovariansi, dan keefektifan pelaksanaan teknik CGB dianalisis menggunakan konversi skor menjadi nilai skala 5. Hasil penelitian tidak ada perbedaan yang signifikan pada motivasi dan prestasi belajar peserta didik yang mengikuti pembelajaran dengan teknik CGB dan  pembelajaran tidak dengan teknik CGB. Penerapan teknik CGB dalam pelaksanaan pembelajaran cukup efektif untuk mencapai tujuan pembelajaran, melihat dari hasil pengisian lembar observasi dan lembar responden untuk keefektifan pelaksanaan pembelajaran.